Use of Technology Acceptance Model and Security in Mobile Banking Usage Behavior Analysis - Putu Deby Cahyani Pramesti; I Gst. Ayu Eka Damayanthi (E-Jurnal Akuntansi, 2024)
The mobile banking service answers the demands of customers who want a safe, fast service, available 24 hours, and can be accessed from anywhere, which is sufficient by means of a cell phone. The purpose of this study is to conduct an empirical study using the Technology Acceptance Model approach by adding a security variable to prove its effect on the behavior of using mobile banking applications. The number of samples used, namely 150 customers with the purposive sampling method, was processed using the Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) with the help of SmartPLS version 4 software. The findings show that perceived ease of use and perceived usefulness have an indirect effect on use behavior through behavioral intention. Meanwhile, security and behavioral intention directly influence use behavior. Overall, the relationship between variables has a positive and significant influence.